Listening to CLIL Practitioners - Jermaine S. McDougald; Daniela Duarte Gómez; Laura Susana Quesada Gutiérrez; Félix Gonzalo Sánchez Córdoba (Colombian Applied Linguistics Journal, 2023)
Content and Language Integrated Learning (CLIL) is an educational approach that combines linguistic and subject-based learning to develop the necessary competencies for success in a globalized world. A mixed-method study researched how CLIL is implemented in (10) K-11 schools in Bogota, Colombia, collecting data from 121 in-service teachers in private schools using an array of instruments, such as surveys, structured interviews, and semi-structured interviews. Using the grounded theory approach, data analysis showed that the participants had limited awareness of the CLIL approach and principles. Accordingly, the findings revealed that there is a need for more focus on fundamental CLIL concepts and more formalized teacher training programs. Furthermore, context-orientated resources also emerged as a priority amongst participants, considering that schools were merely trying to replicate European models of delivering CLIL without clear adaptations or consideration for the voices of local teachers. As a result, bilingual schools in Bogota, which are more inclined to use CLIL-oriented approaches, should establish a network to facilitate CLIL training programs to equip in-service teachers who are immersed in content and language environments.